2017
DOI: 10.1161/circheartfailure.117.003870
|View full text |Cite
|
Sign up to set email alerts
|

NOD2 (Nucleotide-Binding Oligomerization Domain 2) Is a Major Pathogenic Mediator of Coxsackievirus B3-Induced Myocarditis

Abstract: NOD2 is an important mediator in the viral uptake and inflammatory response during the pathogenesis of CVB3 myocarditis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
58
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 71 publications
(61 citation statements)
references
References 32 publications
2
58
0
1
Order By: Relevance
“…Immune cells that contribute to remodelling include mast cells, macrophages (M2 macrophages, also known as alternatively activated macrophages, and myeloidderived suppressor cells), T helper 2 (T H 2) and T H 17 cells and, in the case of autoimmune aetiologies, B cells that produce autoantibodies that form immune complexes with self-antigens and complement components 64,65 . Immune cells release cytokines, such as transforming growth factor-β1 (TGFβ1), IL-4, IL-1β, IL-17A, IL-33 and tumour necrosis factor (TNF), among other mediators, that promote remodelling, collagen deposition and fibrosis [66][67][68][69][70][71] . Fibrosis is a consequence of inflammation at the site of tissue damage and is the characteristic pathological feature of DCM aside from dilatation 8,62 .…”
Section: Inflammationmentioning
confidence: 99%
“…Immune cells that contribute to remodelling include mast cells, macrophages (M2 macrophages, also known as alternatively activated macrophages, and myeloidderived suppressor cells), T helper 2 (T H 2) and T H 17 cells and, in the case of autoimmune aetiologies, B cells that produce autoantibodies that form immune complexes with self-antigens and complement components 64,65 . Immune cells release cytokines, such as transforming growth factor-β1 (TGFβ1), IL-4, IL-1β, IL-17A, IL-33 and tumour necrosis factor (TNF), among other mediators, that promote remodelling, collagen deposition and fibrosis [66][67][68][69][70][71] . Fibrosis is a consequence of inflammation at the site of tissue damage and is the characteristic pathological feature of DCM aside from dilatation 8,62 .…”
Section: Inflammationmentioning
confidence: 99%
“…adaptive immune system, which is associated with diffuse inflammation of the myocardium (3)(4)(5). Activated monocytes, macrophages, and T-and B-lymphocytes derived from secondary lymphoid organs, like the spleen, are thereby recruited into the heart-cardiosplenic axis-to initiate an orchestra of antiviral and inflammatory defense responses (6); however, this immune response can induce cardiac-damaging mechanisms when uncontrolled and hyperactive-for example, cardiac fibrosis-and may progress to dilated cardiomyopathy (7).…”
mentioning
confidence: 99%
“…CVB3 infection also activates the NLRP3 inflammasome (27). However, unlike the closely related enterovirus, EV-A71 (HEV-A genus), for which the NLRP3 inflammasome plays a defensive role against virus infection (18)(19)(20), it was reported that inhibition of caspase-1 activity or knockdown of NOD2 in mice alleviates CVB3-induced myocardial damage (27,28). These observations suggest a possible pathogenic role for NLRP3 inflammasome in CVB3 infection; however, direct evidence is lacking.…”
mentioning
confidence: 99%